Doctors' and nurses' attitudes towards neonatal ethical decision making in Ireland. Issue 3 (17th August 2007) - Samaan, M C; Cuttini, M; Casotto, V; Ryan, C A
Abstract : Objective: To explore the clinical staff attitudes towards ethical decision making in neonatal intensive care units (NICUs) in Ireland, to establish differences between doctors and nurses and to compare attitudes in Ireland with those in Europe. Design: Cross-sectional study by means of an anonymous questionnaire. 64 doctors and 228 nurses in seven NICUs participated (response rates 74% and 81%, respectively). Through factor analysis the staff answers to 12 attitude statements were used to build a score whose range varied from 0 (preservation of life in any case) to 10, indicating a more individualised approach according to the patient's best interests. Main outcome measure: Staff attitudes to ethical decision making in NICU. Results: Mean values of attitude scores were 5.8 (95% CI 5.3 to 6.2) for doctors, and 6.0 (95% CI 5.5 to 6.5) for nurses. Respondents with experience in follow-up of NICU graduates had significantly higher scores (6.7 vs 5.4, p = 0.018), while the opposite was true among more religious staff (5.8 vs 6.9, p = 0.026) and particularly for minority religions such as Muslim (4.1, 95% CI 3.1 to 5.2). Scores were higher after age 30 for nurses, and after age 40 for doctors, suggesting the adoption of a less vitalistic viewpoint as respondents grow older and more experienced. Among doctors, a relationship was found between the attitude score and their self-reported non-treatment practices. Conclusions: In Ireland, NICU doctors and nurses hold similar attitudes towards ethical decision making. Personal and professional factors have a statistically significant impact on attitude score. Compared with the rest of Europe, attitudes in Ireland appear more similar to those of southern rather than northern European countries.